(untitled) (Research, Society and Development, 2021)
During the surgical removal of maxillary molars, tooth or fragment displacement into the maxillary sinus may occur. The presence of foreign bodies inside these cavities leads to complications such as mucoceles, cellulitis, oroantral fistulae and maxillary sinusitis, to prevent the arise and worsening of complications, these events must be addressed in an early stage. This article aims to report the removal of a tooth root from the maxillary sinus, through the modified Caldwell-Luc (CLM) approach and describe the current indications for the Caldwell Luc technique. It reports an upper third molar surgery in which a patient had the distal root of the left superior third molar displaced into the maxillary sinus, later showing signs of sinus opacification and loss of patency of the maxillary ostium obstructed by the root. After antibiotic treatment, the root was recovered through the CLM technique by local anesthesia, without complications. Foreign bodies in the maxillary sinuses must be urgently addressed, avoiding the development of infectious conditions, the CLM approach is the choice approach to manage these complications by a simple and safe way.